Destination Noida a coffee table book - Mitra, Shalini (Noida R Coffee Table Books, 2011)
This book Is and especially designed to provide amazing success of city noida by featuring its development by photography choosing noida for writing a book on, is my belief that all things good should be appreciated unconditionally.
Keywords: Noida (India) -- Pictorial works